Peacebuilding through non-formal education programmes: a case study from Karamoja, Uganda. Issue 2 (15th March 2017) - Datzberger, Simone
ABSTRACT: Experts increasingly refer to the crucial role of education in cultivating processes of sustainable peacebuilding in conflict-affected environments. While peacebuilding interventions have slowly started to place emphasis on aspects of equality or service delivery in formal education systems, the potential of non-formal education (NFE) programmes to foster social transformation in conflict-affected environments often remains unexploited. There is little research examining how NFE can affect the security situation and peace process in a conflict-affected region, or the role it plays in peacebuilding at large. To address these questions, the article draws on the case study of the Alternative Basic Education Karamoja (ABEK) programme in Uganda. It is based on a multi-track data collection strategy involving visits to learning centres, focus group discussions and interviews with government officials, teachers, youth, civil society organizations and other stakeholders over a period of three months in 2015. The study finds that, despite persistent implementation challenges, ABEK proved to (a) be relevant to the security and conflict conditions in the region; and (b) overcome structural and indirect forms of violence through alternative and flexible modes of education. The ABEK case therefore gives rise to much wider peacebuilding implications and formal education sector planning in conflict-affected environments.